Perlindungan Hukum Pekerja Migran: Studi Kasus di The Peninsular And Oriental Steam Navigation Company (P&O Maritime Logistics) Dubai - Dedy Arman Wijaya; Bresca Merina; Idham Ibty; Syamsudin (Jurnal Hukum Caraka Justitia, 2026)
This study aims to analyse the implementation of legal protection for migrant workers in the maritime sector employed at P&O Maritime Logistics, Dubai, United Arab Emirates. Migrant seafarers are exposed to high occupational risks, long working hours, and operational pressures that may affect their occupational safety and welfare. This research applies a qualitative descriptive approach using in-depth interviews with occupational safety and health (OSH) management, ship captains, technicians, and migrant crew members, supported by document analysis. The findings indicate that legal protection has been normatively regulated through international instruments such as the Maritime Labour Convention (MLC) and the International Safety Management (ISM) Code. However, the effectiveness of these protections largely depends on company policies, safety culture, supervision mechanisms, and operational conditions in practice. Although migrant crews possess internationally recognized safety certifications, factors such as work fatigue, the implementation of a customer priority system, and insufficient supervision of working and rest hours may hinder the fulfilment of occupational safety rights. Therefore, strengthening legal protection for migrant seafarers requires integrated compliance with international regulations, safety-oriented corporate governance, and consistent occupational safety and health management.